Juvenile homicide: public perceptions and sentencing considerations - Heilbrun, Kirk (The Routledge international handbook of juvenile homicide, 2024)
This chapter addresses three major topics related to juvenile homicide, committed by individuals who are younger than 18 years at the time of the offense. The topic involves public perceptions that are relevant to the sentencing of convicted individuals. Such public perceptions may be relevant to sentencing, as elected or even appointed judges may be sensitive to such views. The second topic concerns the contributions of risk assessment to such sentencing. Finally, we discuss the recent decision by the US Supreme Court in Jones v. Mississippi (2021). In Jones, the Court held that it was not necessary for the adult trial court to determine that a juvenile convicted of murder was “permanently incorrigible” before sentencing that individual to life without parole, an expectation that was set forth in earlier Supreme Court cases on juvenile resentencing.